Use of services and associated costs for young adults with childhood hyperactivity/conduct problems: 20-year follow-up. (June 2014) - D'Amico, Francesco; Knapp, Martin; Beecham, Jennifer; Sandberg, Seija; Taylor, Eric; Sayal, Kapil
Abstract : Background: Although childhood hyperactivity and conduct problems are associated with difficulties in adulthood, little is known about later service use or public expenditure costs in the UK. Aims: To describe the use of services and calculate recent (past 6 months) and early adulthood (since the age of 18 years) public expenditure costs incurred by young adults who had hyperactivity and/or conduct problems during childhood. Method: A 20-year follow-up of a community sample of 6- to 7-year old boys ( n = 83) with hyperactivity only, conduct problems only, mixed hyperactivity and conduct problems, and no behaviour problems (control). Information was obtained about service use; recent (past 6 months), and early adulthood (since age 18 years) public expenditure costs were calculated. Results: High levels of childhood conduct problems were associated with a two- to threefold increase in early adulthood costs, mainly driven by criminal justice contacts. Although the mixed problems group had the highest recent costs in terms of receipt of benefits and health and social care, they had the lowest criminal justice costs. Conclusions: High levels of early childhood conduct problems are particularly associated with increased health, social care and criminal justice costs in adulthood.